Health Consequences of the Female Genital Mutilation: A Systematic Review: - Sarayloo, Khadijeh; Latifnejad Roudsari, Robab; Elhadi, Amy (Galen Medical Journal, 2019)
Female genital mutilation (FGM) is a general health concern. The World Health Organization has recognized it as a condition that endangers women’s health. This review study aimed to identify the types of health outcomes of FGM. Therefore, a systematic review was conducted to create a critical view of the current evidence on the effect of Female genital on girls and women’s health. In this study, we focused on the health risks of female Female genital. Academic databases such as PubMed, Science Direct, Scopus, Google Scholar, Cochrane Database of Systematic Reviews, SID, IranMedex, Irandoc, and Magiran were searched with regard to the health consequences of FGM from January 1990 until 2018. Eleven review studies met the criteria and contained 288 relevant studies on the risks of FGM. It was suggested that FGM had various physical, obstetric, sexual, and psychological consequences. Women with FGM experienced mental disturbances (e.g., psychiatric diagnoses, anxiety, somatization, phobia, and low self-esteem) than other women. Our study can provide evidence on improving, changing behaviors, and making decisions on the quality of services offered to women suffering from FGM.[GMJ.2019;8:e1336]